PENGARUH STRUKTUR ORGANISASI, KEPEMIMPINAN DAN KOMPETENSI PEGAWAI TERHADAP EFEKTIVITAS PELAYANAN PROGRAM ONE DAY SERVICE DI KANTOR PERTANAHAN KOTA MATARAM - Lalu Parjadinata; Surati Surati; Dwi Putra Buana Sakti (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2020)
One Day Service is processing land clearance in one day in Mataram Agrarian Office Counter. Low capability of employee in terms of using technology devices, work performance, and discipline affect One Day Service Program. This research aim to analyze the influence of organizational structure, leadership and public servants competence to the effectivity of One Day Service. The research conducted in Mataram Agrarian Office with 50 Samples. This data used primer data and seconder data. The Data collection method of the research is done using observation , interview , the spread of the survey/Engineering and a data collection is done with the survey , documentation , and questionnaires. The result of the hypothesis shows that organizational structure and public servants have a positive and significant impact on the service effectivity. However, leadership has a positive impacts but not that significant.In conclusion, the result of this research illustrate that the influence of organizational structure, leadership, and public servants competence in Mataram Agrarian Offices for One Day Service contributes to the effectivity service, accounting for 48 %. However, miscellaneous factors contribute for 51 %.Keywords: Organizational structure, leadership, and public servants competence, the effectivity of One Day Service, Mataram Agrarian Office.